Facilitating the transport and heating transition: Strengthen carbon pricing, introduce a climate dividend, and reduce adaptation costs - Stefan Bach; Hermann Buslei; Lars Felder; Peter Haan (DIW Weekly Report, 2023)
Despite the easing of prices on the energy markets, private households continue to be burdened by elevated prices. The planned increase the planned increase in the carbon price for transport and heating will raise the burden on private households even further. These additional costs are unequally distributed and have a regressive effect, as poor households must spend much more relative to their net income than rich households. Using the tax revenue from carbon pricing to fund a flat-rate climate dividend per person reduces this regressive effect substantially. However, low-income households with a high level of energy consumption, which are impacted in particular, need additional relief or more support in conserving energy. Adaptation responses to the higher prices are uncertain, but could result in emissions savings of up to 30 percent.
Keywords: Q41; D31; H23; 330; Energy prices; distribution; transfer reform